1999
DOI: 10.1128/jvi.73.7.6024-6030.1999
|View full text |Cite
|
Sign up to set email alerts
|

Ebola Virus Can Be Effectively Neutralized by Antibody Produced in Natural Human Infection

Abstract: The activity of antibodies against filoviruses is poorly understood but has important consequences for vaccine design and passive prophylaxis. To investigate this activity, a panel of recombinant human monoclonal antibodies to Ebola virus antigens was isolated from phage display libraries constructed from RNA from donors who recovered from infection in the 1995 Ebola virus outbreak in Kikwit, Democratic Republic of Congo. Antibodies reactive with nucleoprotein (NP), envelope glycoprotein (GP), and secreted env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
164
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 273 publications
(177 citation statements)
references
References 31 publications
7
164
0
3
Order By: Relevance
“…Preference for sGP-binding by these mAbs is likely due to increased exposure of the epitope on sGP compared to GP, possibly owing to partial obstruction on the native trimer of N-terminal (sGPhomologous) residues by MUC or slightly different conformations between the sGP dimer and GP trimer (Yang et al, 1998). Consistent with previous findings, KZ52 bound exclusively to full length GP under competitive conditions as expected since the epitope is known to comprise amino acids present in both GP1 and GP2 (Lee et al, 2008;Maruyama et al, 1999). In contrast to KZ52, JP3K11 exhibited preferential recognition of GP CatL and was the sole mAb to bind GP in its Cat-cleaved conformation; increased exposure times confirmed that no mAb in this panel other than JP3K11 reacted with cathepsinprocessed GP under competitive conditions (data not shown).…”
Section: Neutralizing Antibodies Bind Representative Gp Targets Of Nasupporting
confidence: 86%
See 1 more Smart Citation
“…Preference for sGP-binding by these mAbs is likely due to increased exposure of the epitope on sGP compared to GP, possibly owing to partial obstruction on the native trimer of N-terminal (sGPhomologous) residues by MUC or slightly different conformations between the sGP dimer and GP trimer (Yang et al, 1998). Consistent with previous findings, KZ52 bound exclusively to full length GP under competitive conditions as expected since the epitope is known to comprise amino acids present in both GP1 and GP2 (Lee et al, 2008;Maruyama et al, 1999). In contrast to KZ52, JP3K11 exhibited preferential recognition of GP CatL and was the sole mAb to bind GP in its Cat-cleaved conformation; increased exposure times confirmed that no mAb in this panel other than JP3K11 reacted with cathepsinprocessed GP under competitive conditions (data not shown).…”
Section: Neutralizing Antibodies Bind Representative Gp Targets Of Nasupporting
confidence: 86%
“…Viral polymerase-driven expression from the EBOV GP gene yields a secreted form of GP, sGP, which is the most abundant GP protein synthesized during infection and constitutes greater than 80% of total GP (Volchkov et al, 1998). Its main role in viral pathogenesis is unknown but it is detected at high concentrations in the blood (Sanchez et al, 2001) and is hypothesized to act as an immune decoy (Maruyama et al, 1999) by serving as a target for virus specific antibodies (Wilson et al, 2000). The synthesis of full length virion-bound GP is directed only when the polymerase inserts a non-templated adenosine during transcription.…”
Section: Introductionmentioning
confidence: 99%
“…A caveat to note here is that neutralization is carried out on plaquing virus, although most infectious particles are nonplaquing, as revealed by the correspondence of the challenge dose of 300LD 50 to only 10 pfu of virus. Using a potent human neutralizing anti-Ebola antibody (Parren et al, 2001a), we found that protection against a guinea pig-adapted virus in a guinea pig model required serum antibody concentrations corresponding to essentially complete virus neutralization in vitro (Maruyama et al, 1999;Parren et al, 2001a). In this case, the viral challenge was much higher (10 4 pfu; >10 5 LD 50 ) than the previous example (10 pfu; 300 LD 50 ).…”
Section: G Filovirusesmentioning
confidence: 99%
“…There is some evidence that some cross-reactivity between Ebola subtypes is observed in ELISA assay tests [14,31,32]. Fig.…”
Section: Cross-reactivity Between Strainsmentioning
confidence: 99%